The impact of weather patterns on increasing violent crime and social cost in South Africa - Tianen Yao; Jinjia Zhang; Xinyu Yang; Yida Wang; Huaixiao Ye; Zhenyu Zhang; Ming Xu (Humanities & Social Sciences Communications)
Abstract Crimes in South Africa are characterized by more violent crimes, more frequent in warm seasons, and more in Gauteng Province. We propose interpretable machine learning (IML) and multiple linear regression (MLR) algorithms to quantify the determinants of crime. From 2017 to 2023, the total number of crimes decreased by 974.8 cases per quarter, but violent crimes continued to increase (694.8 cases per quarter). Meteorological factors accounted for 64% of the contribution to violent crime, greater than that of property crime (44%). Notably, air temperature and precipitation may increase violent crime by 0.41% (95% CI: 0.38%, 0.44%) and 33% (95% CI: 31%, 34%) in the warm season. PM2.5 pollution leads to a 2.1% increase in violent-related crime, indicating a marginally significant impact on human activity. South Africa’s international homicide (IH), as a severe violent crime, reached the top in 2021 worldwide. Based on the IML, per capita income plays a leading role in IH. The social cost of IH reaches USD 838.49 million, with the climate-induced factor accounting for USD 503.09 million (60%). Despite differences in the economic and climatic contexts of Chicago’s urban crime data and Mexico’s crime records, the findings remain valid, revealing universal patterns of crime and the impact of climate change. We therefore recommend that economic development, together with the mitigation of climate and environmental pollution, can effectively reduce criminal activities and thus contribute to sustainable social development.